Manual on Statistics of International Trade in Services 2010 : (MSITS 2010) - United Nations. Statistical Division (Geneva ; New York : United Nations, 2012)
The manual sets out an internationally agreed framework for the compilation and reporting of statistics of international trade in services in a broad sense, which addresses the needs, including those of international trade negotiations and agreements, for more detailed , more comparable and more comprehensive statistics on this type of trade in its various forms.
"ST/ESA/M.86/Rev.1."
Includes bibliographical references and index.
rua 04/11/13
Loans
Keywords: Service industries -- Statistics -- Handbooks, manuals, etc; International trade -- Statistics -- Handbooks, manuals, etc